Moral reasoning and action in war - Underwood, R (2019)
The moral reasons we have to kill some people and not others in service to morally important outcomes – like winning a just war – are the central concern of this thesis. The three papers that comprise this thesis argue that reductive moral reasons – reasons derived from the ethics of individual self and other defense – apply in war and should figure in the individual and joint deliberation of soldiers when they decide whom they ought morally to kill. The focus on reductive moral reasons also aims to explain and defend “revisionist” just war theory and the philosophical methodology underpinning it known as “reductivism.” The explanations and defense respond to some familiar criticisms of revisionist just war theory. Each paper also defends a central idea of revisionist just war theory and reductive individualism. That is, that the morally best option in collectivized war is the morally best option in other contexts: distribution of unavoidable harms to those who bear the most responsibility for the circumstances in which those harms arise. The first paper defends revisionist just war theory and reductive individualism from the charge that it discounts the collective and political nature of war. First, it argues that any appeal to collective action tacitly appeals to individual morality in order to square with our intuitions about intentional defensive killing. Second, it argues that moral reasons derived from political self-determination either do not matter in war, or will not matter enough to override those reasons we can derive from the distribution of unavoidable harms to those who bear the most responsibility for the circumstances in which those harms arise. The second paper defends the relevance of revisionist just war theory to the way soldiers and armies fight. The paper does this by demonstrating that reductive individualism is the best way to account for the fact that soldiers kill in war to communicate reasons for action to their enemies. The final paper defends the relevance of revisionist just war theory to moral deliberation under the conditions of uncertainty. The paper develops an expanded understanding of the necessity constraint and adapts the comparative dimension of liability to a decision theoretic approach to acting under the conditions of uncertainty.